PENGARUH VIDEO PEMBELAJARAN INTERATIF TERHADAP HASL BELAJAR SISWA PADA MATA PELAJARAN INFOTMATIKA KELAS XI SMA KRISTEN MAKALE - Makkalo, Lisda; Anna Pertiwi; Hasni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to see the influence of interactive learning videos on learning outcomes at Makale Christian High School. Based on the initial observations made and the results of interviews with teachers of Informatics subjects, it was revealed that the learning outcomes of grade XI students still needed to be improved, because there were still some students who obtained scores below the minimum completeness criteria (KKM) of 70, according to the standards set by the school, in the mid-semester exam. This low learning outcome is often caused by the choice of inappropriate learning media by the teacher, so that students are less enthusiastic in participating in learning and do not give full attention to the teacher who is teaching. This study uses a quantitative method with an experimental approach. The population in the study is all students of Makale Christian High School in class XI which totals 205 students consisting of six classes, namely classes XI.A-F. The sampling technique uses purposive sampling. Data collection techniques use observation, pretest and posttest. The data analysis technique uses validity and reliability tests, normality tests, homogeneity tests and hypothesis tests. The findings of the study showed that in the experimental class with an average pretest score of 51.83, there was an increase to 73.33 in the posttest, with a Sig.(2-tailed) value of 0.00 less than 0.05. Thus, it can be said that interactive learning videos have an influence on student learning outcomes in grade XI of Informatics at Makale Christian High School.